A systematic study of harnessing low-temperature geothermal energy from oil and gas reservoirs - Liu, Xiaolei; Falcone, Gioia; Alimonti, Claudio (Nature Publishing Group, 2017)
Mature hydrocarbon fields co-produce significant volumes of water. As the produced water increases over the life of the field, the project's operating costs increase (due to greater water management expenditure), while the oil revenues decrease. Typically, these waste streams of water have temperatures of 65–150 °C. The combination of moderate temperatures and large water volumes may be suitable for electricity generation and/or district heating. Being able to capture the geothermal energy from existing hydrocarbon fields could extend their lifespan by delaying their economic cut-off point. In this paper, mature oil and gas reservoirs worldwide are critically reviewed, where waste heat recovery has already been tested, or its potential identified. A roadmap of screening criteria based on geological, reservoir, production and economic parameters is then proposed, to assess how, where and when low-temperature waste heat recovery is feasible. The roadmap is tested against the Villafortuna–Trecate oil field in Italy, where the aquifer not only provides pressure support to the reservoir, but also represents a natural, in-situ hydrothermal resource. The results suggest that a single-well could recover approximately 25 GWh of electric power over a 10-year period, with an installed capacity of 500 kW.
Keywords: low-temperature geothermal resources; Geothermal co-production; Mature hydrocarbon fields